2016
DOI: 10.1021/acs.langmuir.6b01922
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface Properties of Poly(methyl methacrylate) Film Using Poly(perfluoromethyl methacrylate)s with Short Perfluorinated Side Chains

Abstract: To control the surface properties of a commonly used polymer, poly(methyl methacrylate) (PMMA), poly(perfluoromethyl methacrylate)s (PFMMAs) with short perfluorinated side groups (i.e., -CF3, -CF2CF3, -(CF3)2, -CF2CF2CF3) were used as blend components because of their good solubility in organic solvents, low surface energies, and high optical transmittance. The surface energies of the blend films of PFMMA with the -CF3 group and PMMA increased continuously with increasing PMMA contents from 17.6 to 26.0 mN/m, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…PFPMA with a short fluorinated side group was strategically used; despite their very low surface energies of 8–10 mN/m, acrylic polymers with long fluorinated side groups (number of fluorocarbon units ≥8) pose a potential environmental risk of bioaccumulation. Nevertheless, the surface energy of poly­(PFPMA) has a very low value of 12.6 mN/m . In addition, it was reported that a poly­(PFPMA) coating increases the transmittance of a glass slide . Therefore, a broad range of the controllable surface and optical properties can be obtained by adjusting the ratio of PFPMA and the other monomers.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…PFPMA with a short fluorinated side group was strategically used; despite their very low surface energies of 8–10 mN/m, acrylic polymers with long fluorinated side groups (number of fluorocarbon units ≥8) pose a potential environmental risk of bioaccumulation. Nevertheless, the surface energy of poly­(PFPMA) has a very low value of 12.6 mN/m . In addition, it was reported that a poly­(PFPMA) coating increases the transmittance of a glass slide . Therefore, a broad range of the controllable surface and optical properties can be obtained by adjusting the ratio of PFPMA and the other monomers.…”
Section: Introductionsupporting
confidence: 79%
“…Fluorine-containing polymers are attractive materials that can satisfy the wettability and transparency requirements of surfaces because of their low surface energy and low reflective index. , Moreover, they exhibit outstanding properties such as unique water and oil repellency, self-cleaning capability, excellent thermal and chemical stability, and low dielectric constant. On the other hand, the practical applications of fluorine-containing polymers are limited by their low solubility in common solvents, low compatibility with hydrocarbon polymers, low adhesion to any substrate, and high cost. Copolymerization with various monomers has been explored as an alternative to overcome these limitations. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though only 1 wt% PFPE-BP is used in the coating solution, the anti-reflective and anti-contamination abilities of the coating are significantly enhanced. This is because the PFPE moiety is aligned along the top surface of the coating layer 30 , thus affording the anti-reflective and anti-contamination surface properties of PFPE even at low loading. To confirm this, surface analysis using X-ray photoelectron spectroscopy (XPS) was performed ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, such copolymers should contain additional hydrophobic comonomers, such as styrene (S) or tricyclodecyl methacrylate, that have bulky and hydrophobic pendant groups. Accordingly, fluorinated and silyl comonomers have been applied in several cases to increase hydrophobicity and decrease the moisture absorption of PMMA. However, despite numerous attempts, addressing the drawbacks of PMMA while maintaining its high transmittance remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%